The Role of Police Investigators in Implementing Restorative Justice for Children Involved in Narcotics Crimes - Hoirul Rohman; Irawan Soerodjo; Dudik Sjaja Sidarta (International Journal of Social Welfare and Family Law, 2026)
The handling of children involved in narcotics crimes requires a restorative approach focused on rehabilitation rather than punishment. This study aims to examine the role of police investigators in applying restorative justice to child offenders in narcotics cases and to identify the obstacles encountered in its implementation. This research employs a normative legal research method with statutory and conceptual approaches. Primary legal materials include Law Number 11 of 2012 on the Juvenile Criminal Justice System, Law Number 35 of 2009 on Narcotics, and Chief of Police Regulation Number 8 of 2021. The findings show that investigators play a strategic role in facilitating diversion, including conducting initial assessments, facilitating diversion deliberations, and coordinating with supporting institutions such as the Correctional Center (Bapas), National Narcotics Agency (BNN), and Social Services. However, implementation remains suboptimal due to internal constraints, including inadequate training and understanding among investigators, limited facilities such as child-friendly rooms and mediation spaces, regulatory disharmony between the Juvenile Criminal Justice System Law and the Narcotics Law, weak inter-agency coordination, and lack of support from families and communities. Post-diversion monitoring is also ineffective. This study concludes that strengthening investigator capacity through specialized training, improving legal frameworks through regulatory harmonization, and enhancing inter-agency collaboration are essential to ensure restorative justice truly serves the best interests of children.